AN ANALYTICAL LOOK AT THE PROGRAMS OF THE DEPARTMENT OF GEOGRAPHY OF THE CREATION OF THE CHEIKH ANTA DIOP UNIVERSITY TO THE PRESENT DAY - CAMARA, EL HADJI HABIB; SARR, Libasse Hann (Advances in Social Sciences Research Journal, 2020)
Pedagogy at the university level remains, in Senegal, a field little invested in the framework of research in the sciences of education. This work seeks to explore the "long march" of programs in terms of evolution of the contents to be taught from the Department of Geography of the University Cheikh Anta DIOP of Dakar since the creation of the university in 1957 to the present day. It focuses more specifically on the analysis of these programs, which form the basis of any educational project, by using various tools, specifically pre-defined analysis grids, to determine whether these programs are operational or not. as part of the conceptualization-epistemic and pragmatic-registers in their contents.